Regulation of immune cells by miR-451 and its potential as a biomarker in immune-related disorders: a mini review - Wang, Fei-xiang; Shi, Zu-an; Mu, Guo (Frontiers in Immunology, 2024)
In 2005, Altuvia and colleagues were the first to identify the gene that encodes miR-451 in the human pituitary gland, located in chromosome region 17q11.2.Subsequent studies have confirmed that miR-451 regulates various immune cells, including T cells, B cells, microglia, macrophages, and neutrophils, thereby influencing disease progression. The range of immune-related diseases affected encompasses various cancers, lymphoblastic leukemia, and injuries to the lungs and spinal cord, among others. Moreover, miR-451 is produced by immune cells and can regulate both their own functions and those of other immune cells, thus creating a regulatory feedback loop. This article aims to comprehensively review the interactions between miR-451 and immune cells, clarify the regulatory roles of miR-451 within the immune system, and assess its potential as both a therapeutic target and a biomarker for immune-related diseases.